Značaj biomarkera plazme u predviđanju srčanog zastoja kod pacijenata sa akutnim infarktom miokarda: Plasma Biomarkers Predicting Heart Failure Post Heart Attack - Rong, Guihong; Wang, Xiao; Qin, Xinling; Wang, Yanxia; Quan, Meilian; Xi, Chunfeng (Journal of Medical Biochemistry, 2024)
Background: Acute myocardial infarction (AMI) is characterized by high mortality and disability rates. Timely and effective revascularization has saved the lives of many patients. However, some patients develop complications such as heart failure (HF) following myocardial infarction, which significantly affects their quality of life and may even be life-threatening. Therefore, the search for effective biomarkers to predict the occurrence of HF after AMI, along with early prevention and treatment strategies, will greatly improve clinical outcomes for patients with post-myocardial infarction HF Methods: A total of 170 patients with acute myocardial infarction (AMI) were enrolled in this study, including 44 patients with post-AMI heart failure (HF) and 126 patients with post-AMI non-HF. We measured the serum biomarkers NT-proBNP, cTNT, PLR, NLR, and GDF-15 in all patients using enzyme-linked immunosorbent assay (ELISA). Subsequently, we performed t-tests to assess the predictive value of these biomarkers for post-AMI heart failure (HF). Results: In the group of HF patients, cTNT, NT-proBNP, GDF-15 and NLR was significantly higher than in the group without HF, but PLR was not .The AUC of NLR to predict HF after AMI was 0.632 (95%CI:0.542-0.723), P=0.010, with a cut-off value of (3.86×109)/L , GDF-15 was 0.661 (95%CI0.560-0.763), P=0.002, with a cut-off value of 1.35 ng/mL, and NT-proBNP was 0.82 (95%CI0.723-0.876), P<0.001, with a cut-off value of 1444 pg/mL. Conclusions: In five biomarkers, there is predictive value in NT-proBNP , NLR, GDF-15 for patients with HF after AMI .